Adequate calcium intake during long periods improves bone mineral density in healthy children. Data from the Childhood Obesity Project. Issue 3 (June 2018) - Closa-Monasterolo, Ricardo; Zaragoza-Jordana, Marta; Ferré, Natàlia; Luque, Veronica; Grote, Veit; Koletzko, Berthold; Verduci, Elvira; Vecchi, Fiammetta; Escribano, Joaquin; ,
Summary: Background: Bone mineralization can be influenced by genetic factors, hormonal status, nutrition, physical activity and body composition. The association of higher calcium (Ca) intake or Ca supplementation with better bone mineral density (BMD) remains controversial. Furthermore, it has been speculated that maintaining long-term adequate Ca intake rather than having a brief supplementation period is more effective. The aim of the study was to prospectively analyse the influence of adequate Ca intake on BMD at 7 years of age in European children. Methods: Data from the Childhood Obesity Project were analysed in a prospective longitudinal cohort trial. Dietary intake was recorded using 3-day food records at 4, 5 and 6 years of age. The probability of adequate intake (PA) of Ca was calculated following the American Institute of Medicine guidelines for individual assessments, with FAO, WHO and United Nations University joint expert consultation dietary recommendations. Children were categorised as having high Ca PA (PA >95%) or not (PA <95%). At 7 years, whole body (WB) and lumbar spine (LS) BMD were measured in the Spanish subsample by dual-energy x-ray absorptiometry. Internal BMD z-scores were calculated; BMD below −1 z-score were considered to indicate osteopenia, and BMD z-scores below −2, "low bone mineral density for age". Results: BMD was measured in 179 children. Ca intake at 6 years was positively correlated with LS BMD at 7 years (R = 0.205, p = 0.030). A Ca increase of 100 mg/day explained 19.4% (p = 0.011) of the LS BMD z-score variation, modifying it by 0.089 (0.021, 0.157) units. Children with Ca PA >95% at 5 and 6 or from 4 to 6 years of age showed higher BMD z-scores at the LS and WB levels than children with Ca PA <95% (p < 0.001 and p < 0.05 for LS and WB BMD, respectively). Ca PA >95% maintained over 2 years explained 26.3% of the LS BMD z-score variation (p < 0.001), increasing it by 0.669 (0.202, 1.137). PA >95% maintained over 3 years explained 24.9% of the LS BMD z-score variation, increasing it by 0.773 (0.282, 1.264). The effects of Ca adequacy on WB BMD were similar. Children with PA >95% over 2 years had an Odds ratio of 13.84 and 12 for osteopenia at the LS and WB levels, respectively (p = 0.001). Conclusions: Long periods of adequate Ca intake in childhood increase BMD and reduce osteopenia risk. The Childhood Obesity Project clinical trial (CHOP) was registered at clinicaltrials.gov asNCT00338689 .